Response of leaf area and dry matter of crop, weeds and cover crops to competition and fertilizer resources - Fahimeh DADASHI; Faezeh ZAEFARIAN; Rahmat ABBASI; Mohammad Ali BAHMANYAR; Mohammad REZVANI (Acta Agriculturae Slovenica)
Plasticity of plants to allocate leaf area and dry matter to upper layer of canopy play important role in canopy architecture and competition. In order to study the vertical distribution of leaf area and dry matter of corn (Zea mays L.), cover crops and weeds canopy in different fertilizer condition and competition, a randomized complete block design experiment with 8 treatments and 3 replicates was conducted at Sari Agricultural Sciences and Natural Resources University in 2012. Treatments were included corn with soybean (Glycine max (L.) Merr.) as cover crop without fertilizer application, corn with soybean as cover crop with chemical fertilizer application, corn with soybean as cover crop with compost fertilizer application, corn with wheat (Triticum aesitivum L.) as cover crop without fertilizer application, corn with wheat as cover crop with chemical fertilizer application, corn with wheat as cover crop with compost fertilizer application and corn monoculture both in weedy and weed free conditions. The results showed that weed infestation reduced total leaf area and dry matter of corn. Corn distributed more leaf area and dry mater of canopy to the upper layer in weedy conditions. Between cover crops, soybeans allocated corn leaf area and dry mater to the higher layers of canopy than wheat. Also, soybean reduced leaf area and dry mater production of weeds more than wheat. Soybean as cover crop with the use of compost treatment was more efficient in reducing of weed biomass and corn yield production.